Primary Sjögren's syndrome with multiple calcifications in parotid glands - Keisuke Kondo; Takahiro Kaneko; Norio Horie (Clinical Case Reports, 2019)
Abstract Dispersed calcifications in bilateral parotid glands may strongly suggest Sjögren's syndrome (SS), since the occurrence of bilateral calcifications in other salivary gland diseases is rare. This association between parotid calcifications and SS would thus represent highly useful information for the diagnosis of SS.